Calculation of thermodynamic properties and transport coefficients of CO2–O2–Cu mixtures. (2nd August 2017) - Guo, Xiaoxue; Li, Xingwen; Murphy, Anthony B; Zhao, Hu
Abstract: The thermodynamic properties and transport coefficients of CO2 –O2 –Cu gas mixtures in the temperature range from 300 K to 30 000 K and the pressure range from 0.1 to 0.8 MPa are calculated. Special attention is paid to the influence of different oxygen and copper proportions and different gas pressures on the CO2 –O2 –Cu mixture properties. It can be concluded that the addition of oxygen has a strong influence on both thermodynamic properties and transport coefficients. A small proportion of Cu does not lead to a significant change to the properties, apart from the electrical conductivity at low temperatures. However, Cu mole fractions above 10% start to affect all properties. Increasing gas pressure can cause an increase in the transport coefficients, especially in the high-temperature range. The calculation results provide the necessary data for the further study of the behaviour of plasmas using magnetohydrodynamics arc models. The results can be also used to optimize the ratio of the component gases for different applications; some examples are presented.